Overhaul maintenance of modern bulldozers with software-based management techniques (PERT/CPM) - SELVAN, M MUTHAMIL; AHUJA, SANGEETA; PARRAY, ROAF AHMAD; RAJAIAH, P; RANGASAMY, K (The Indian Journal of Agricultural Sciences, 2015)
Software programs on programme evaluation and review techniques (PERT) and critical path method (CPM) techniques have been developed to analyze the major overhauling of modern bulldozers. The knowledge of time and cost involved in a particular repair activity is essential to decide whether to continue the interrupted work and to assess whether or not it is possible to complete field operation within the stipulated time. These techniques identified forty two subsystems or activities. An analytical programme was subsequently worked out for the various operations related to major overhauling of bulldozer. The expected completion of all events required 192 hr with a variance of 8 hr. The analysis revealed that the probability of completing the overhauling ranged from 0.299 to 0.331 for completionduration of 185 to 200 hr respectively. The algorithms developed through software programs for major overhauling of bulldozer proved their superiority in the validation.